Placental growth hormone in diabetic pregnancy. (16th November 2010) - Higgins, M; Russell, N; Brazil, D; McAuliffe, F
Abstract : Placental growth hormone (PGH) is the main growth hormone in pregnancy. It was thought to be only found in maternal serum and to act mainly through its actions on Insulin Like Growth Factor 1. The aim of this study was to investigate the action of PGH in non-diabetic (ND) compared to Type 1 Diabetic (T1DM) pregnancies. Maternal samples were obtained from 25 ND and 25 T1DM consenting mothers at 36 weeks gestation. Cord blood was obtained from the umbilical vein after delivery of the baby. PGH was measured using ELISA. Statistical analysis was performed using SPSS 16. There was no difference in maternal age, parity, mode of delivery, gender of infants or birth weight between the groups. Placental growth hormone was detected in cord serum. To our knowledge this is the first study to detect PGH in cord blood in infants of diabetic mothers. In the T1DM group, maternal PGH correlated with both antenatal fetal weight and birth weight, suggesting a significant role for PGH in growth in diabetic pregnancies. This relationship may be independent of current conventional measures of glycemic control. Non diabetic (n=25) T1DM (n=25) p Maternal PGH 10639.4 (322.09–89 121.8) 9822.9 (1293.2–86 679.6) 0.7 Cord 164.72 (31–1796) 219.9 (10–1208) 0.5 PGH In the T1DM alone, maternal PGH significantly correlated with ultrasound estimated fetal weight (r=0.4, p=0.02), birth weight (r=0.51, p<0.05) and birth weight centile (r=0.41, p=0.03). Neither maternal nor cord PGH correlated with HbA1c.